Flawson 2021 / Muhamad Aiman Afiq Mohd Noor - Mohd Noor, Muhamad Aiman Afiq (Faculty of Art and Design, 2021)
Imagination or idea is a novelty that arises to distinguished sculptors in a practice of making a new artwork. Being new, in this new found field for this exhibition, the idea of making sculpture is an arduous task which involves a different set of mediums. The mix of found object and concrete has been used in finding newness in shaping a sculpture. The assemblage process generated by the selected found object is to get a desired composition and also acts as the basis for many surrealist objects. The found object literally related to the artist as well as his experience and background is to explore those possibilities. Found object is a natural or man-made object, or fragment of an object, that is found or sometimes bought and kept because of some intrinsic interest by the artist. Moulded concrete is a beautiful material and when applied in the middle of the found object, it produces some lines and different textures that give the artist satisfaction to work with. The use of concrete was proposed to light up directly from the artist and consequently to be more cerebral than just an abstract art. Concrete use is often composed of basic elements such as forms, textures, planes, colors, and structure. In order for finishing, the whole composition is the assemblage, based on found objects and moulded concrete represents the unfinished effect and also a rhythmic texture. Sentiments tend to be absent from concrete but the combination of found objects reveals the emotions, feel and a little bit of emphasis of distortion will create the effect that is impactful.